Pemanfaatan Lahan Pekarangan Pondok Pesantren Nurul Islam Sekarbela Kota Mataram Menggunakan Sistem Agroforestri - Jannah, Husnul; Harisanti, Baiq Muli; Masiah, Masiah; Nurhidayati, Siti; Karmana, I Wayan (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
Partners are in the city of Mataram, namely the Nurul Islam Sekarbela Islamic boarding school. Starting from the problems of the boarding school, including the low level of independent health of students who are staying and also supported by economic needs in the management of Islamic boarding schools, on the other hand, the cottage has a fairly large yard/land but is still not managed optimally. In our service activities, we provide two things that become solutions to the problems of partners at the Nurul Islam Islamic Boarding School, namely by providing education on the application of land management / boarding school yards with the Agroforestry system. Agroforestry system is a system of land / yard management by combining farming, forestry and animal husbandry systems. This system will increase land productivity while conserving land, promoting aesthetics with flowering plants, and the farm that we will combine is trigona bee cultivation. In the aspect of cultivation, we will combine agricultural and forestry crops and choose bee-feeding plants, namely resin and pollen supply plants. Meanwhile, from the aspect of cultivation, the team provided assistance in providing flowering tree seeds of the Kaliandra species, etc. The service implementation team held technical guidance activities on how to plant on peat land for the right types of trees and planting patterns.